Study on attenuation characteristics of electromagnetic waves in plasma-superimposed artificial wave vector metasurface structure. (5th December 2019) - Zhang, Wenyuan; Xu, Haojun; Song, Zhijie; Han, Xinmin; Wei, Xiaolong; Wu, Xin; Li, Yiwen
Abstract: Because of the limitations of thin-layer plasma for electromagnetic wave attenuation, a new PS-AWV (plasma-superimposed artificial wave vector) metasurface structure is proposed. We also introduced the design principle of increasing the propagation distance of electromagnetic waves in plasma using artificial wave vector metasurface. We designed a X band artificial wave vector metasurface by geometric phase dispersion control such that the incident electromagnetic wave abnormally reflected, and the reflection angle reached 55° when measured at normal incidence. Using an electromagnetic finite element method, we established a coupling model of the PS-AWV metasurface structure attenuated electromagnetic wave using CST (Computer Simulation Technology). We analyzed the variation law of reflectivity under different plasma parameter distribution, and the experiment was performed in a microwave darkroom. We also measured the reflectivity of the wave-vector metasurface structure. Both simulation and experimental results show that the artificial wave vector metasurface can effectively increase the attenuation effect of plasma on electromagnetic waves and improve the attenuation effect of electromagnetic waves because of thickness reduction; thus, it can reduce the plasma thickness required for plasma stealth and improve its application in practical scenarios.